A spatial design network analysis of street networks and the locations of leisure entertainment activities: A case study of Wuhan, China. (January 2019) - He, Sanwei; Yu, Shan; Wei, Ping; Fang, Chuanglin
Highlights: Leisure entertainment facilities have differing point, ring, and ribbon patterns. Severance and efficiency are two promising parameters measuring street networks. Leisure entertainment activities and street configurations are spatially correlated. Spatial equity should be emphasized in the process of leisure-based urban planning. Abstract: This paper examines the spatially stratified association between various urban leisure entertainment activities and street configurations via a spatial design network analysis and attempts to provide insightful implications for the sustainable development of a city by using a typical inland city of China, Wuhan, as an example. The street network is characterized by performing a spatial network analysis of the closeness, betweenness, severance and efficiency parameters. The kernel density estimation (KDE) method is employed to measure the proximities of every place to various types of leisure entertainment facilities. The two sets of densities are then analyzed to determine whether spatially stratified correlations exist and whether various leisure entertainment facilities are more spatially correlated with specific street features. The results indicate that a good street network design can be measured not only by closeness or betweenness but also by severance and efficiency. Four street network metrics are spatially correlated with the locations of leisure entertainment activities. Various types of leisure entertainment activities have distinct locational preferences for street networks (e.g., chess and card rooms favor closeness). The conclusions of this paper can help urban planners and policy-makers spatially optimize street networks and leisure venues to develop a sustainable city.